The Eroding Legislative Oversight: The Governance Implications of State Asset Transfers Under Indonesia’s National Capital Law - Syarif Hidayat (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2026)
The enactment of Law Number 3 of 2022 concerning the National Capital (IKN Law) introduced fundamental changes to the legal framework governing state financial management in Indonesia, particularly regarding the authority over the transfer of state-owned assets (Barang Milik Negara, BMN). One of the most significant changes is the elimination of the requirement for prior approval by the House of Representatives (DPR) in asset transfer decisions, which had previously functioned as a key legislative check on executive financial decisions. This paper employs normative legal research through doctrinal and statutory analysis to examine the legal shift in DPR’s authority and its broader implications. The findings reveal that the shift reflects a strategic policy move to facilitate asset-based financing for the accelerated development of Indonesia’s new capital city, designated as a super-priority national project. The government aims to optimize BMN utilization for infrastructure financing by simplifying the approval process. Nevertheless, this regulatory change raises critical legal concerns. First, it generates normative tension between the IKN Law and existing statutory regimes, notably the State Treasury Law. Second, it reduces institutional oversight, potentially undermining transparency and public accountability in BMN transfers. Third, revenues from asset transfers are not automatically earmarked for the National Capital project but remain subject to the state budget allocation process, thus introducing fiscal uncertainty.